2012
DOI: 10.1371/journal.pone.0050520
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolomic Profile of Umbilical Cord Blood in Neonatal Hypoxic Ischaemic Encephalopathy

Abstract: BackgroundHypoxic ischaemic encephalopathy (HIE) in newborns can cause significant long-term neurological disability. The insult is a complex injury characterised by energy failure and disruption of cellular homeostasis, leading to mitochondrial damage. The importance of individual metabolic pathways, and their interaction in the disease process is not fully understood. The aim of this study was to describe and quantify the metabolomic profile of umbilical cord blood samples in a carefully defined population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 59 publications
7
82
1
5
Order By: Relevance
“…We excluded neonates with evidence of perinatal infection, metabolic or congenital abnormalities. This study was a retrospective analysis of two cohorts of neonates prospectively recruited to cEEG studies of neonates at high risk of seizures 4, 15. The modified Sarnat score (Levene) for HIE was performed in all neonates at 24 hours after birth during recruitment of both studies.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded neonates with evidence of perinatal infection, metabolic or congenital abnormalities. This study was a retrospective analysis of two cohorts of neonates prospectively recruited to cEEG studies of neonates at high risk of seizures 4, 15. The modified Sarnat score (Levene) for HIE was performed in all neonates at 24 hours after birth during recruitment of both studies.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging studies on animal model have highlighted the importance to recognize the metabolic fingerprint in perinatal anoxia-hypoxia (19)(20)(21). In newborns with perinatal asphyxia, a small number of metabolomics studies have been published in the literature (22)(23)(24)(25)(26)(27); each of them has depicted the metabolic snapshot of the disease. As recapitulated in a recent review (28), human metabolomics studies have found that the most impaired molecular pathway during perinatal asphyxia and TH are the TCA cycle and the osmoregulation system.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted metabolomic analysis showed a significant alteration between study groups in 29 metabolites from 3 distinct classes (amino acids, acylcarnitines, and glycerophospholipids). A logistic regression model using five metabolites clearly delineates severity of asphyxia andclassifies HIE infants with area under the curve (AUC) = 0.92 [16].…”
Section: Hypoxic Ischemic Encephalopathymentioning
confidence: 99%